Fentanil – Esperienze dal fronte - Daffini, Linda; Praticò, Liliana; Riglietta, Marco (Mission - Open Access, 2024)
In March 2024 the “National Plan of prevention to tackle Fentanyl misuse and other synthetic opioid” was published by the Minister of Health in Italy. Despite the increasing number of overdoses associated with Fentanyl misuse in other countries, such as USA and Canada, this phenomenon is still limited in Italy. Few data are available and the experience in the management of these cases is still poor in the addiction treatment services. The internet represents one of the main sources of information both in terms of scientific literature and ‘grey literature’ provided by people who use drugs. Erowid is a great example of harm reduction resource based on patients’ direct experience and scientific contributions from health professionals.